Influence of Long-Term Freezing of Carcasses in Pre- and Post-Rigor Mortis Stages on the Technological and Nutritional Parameters of the Longissimus lumborum Muscle of Botucatu Rabbits - Dutra, Daniel Rodrigues [UNESP]; Villegas-Cayllahua, Erick Alonso [UNESP]; Baptista, Giovanna Garcia [UNESP]; Ferreira, Lucas Emannuel [UNESP]; Cavalcanti, Érika Nayara Freire [UNESP]; Carneiro, Nívea Maria Gomes Misson [UNESP]; Dias, Ana Veronica Lino [UNESP]; Francelino, Mainara Carolina [UNESP]; Pereira, Mateus Roberto [UNESP]; Castilha, Leandro Dalcin; Borba, Hirasilva [UNESP] (MDPI, 2024)
The aim was to assess the impact of long-term storage on the quality of Botucatu rabbit meat frozen in pre- and post-rigor stages. The stability of the technological and nutritional parameters of Longissimus lumborum (LL) muscle was analyzed over 12 months. In the post-rigor phase, the dorsal LL surface showed a higher level (p < 0.05) of redness and saturation, while the ventral surface showed a higher level (p < 0.05) of yellowness compared to the pre-rigor LL muscle. During storage, the redness and saturation in the LL muscle decreased (p < 0.05), while the yellowness increased (p < 0.05) on both dorsal and ventral surfaces. In the first six months, the pre-rigor meat had a higher pH (p < 0.05) compared to the post-rigor meat. The fresh meat showed higher (p < 0.05) shear force values in the post-rigor stage. Over the 12-month study period, the lipid oxidation, myofibrillar fragmentation index, gross energy, and levels of protein, fat, and carbohydrates increased (p < 0.05), while the shear force, mineral content, and moisture decreased (p < 0.05). Thus, rigor mortis affects meat color in Botucatu rabbits. Fresh meat in the pre-rigor stage is softer, moister, and less acidic than post-rigor meat after 24 h of chilling. Long-term freezing enhances tenderness, regardless of the rigor phase at freezing, preserving its physical, chemical, and nutritional quality, with minor changes in color, lipid oxidation, and chemical composition.
Keywords: meat quality; meat science; Oryctolagus cuniculus; rabbit meat; storage; tenderness